4x5 + 6x2 + 6x3 + 9
2x2 (2x3 + 3) + 3 (2x3 + 3)
Simplify to get your answer:
(2x2 + 3) (2x3 + 3)
6x3 + 9x2 - 2x2 - 3x Before any grouping, take out the common factor, x, to give x*(6x2 + 9x - 2x - 3) = x*[3x*(2x + 3) - 1*(2x + 3)] = x*(2x + 3)*(3x - 1)
If that's + 6x3, the answer is x(x - 6)(x + 6)(x + 6) or x(x - 6)(x + 6)2
6x³ +12x + 18 = 6(x + 1)(x² - x + 3)
-6x3 + 4x7 - 0.8x2 + x4 - 5x5 = 4x7 - 5x5 + x4 - 6x3 - 0.8x2 = x2 (4x5 - 5x3 + x2 - 6x - 0.8)
They are 6x1, 6x2, 6x3 and so on until 6x15.They are 6x1, 6x2, 6x3 and so on until 6x15.They are 6x1, 6x2, 6x3 and so on until 6x15.They are 6x1, 6x2, 6x3 and so on until 6x15.
6x3 - 5x = x*(6x2 - 5)
6x3 - 27x2 + 3x + 36 = 3 (x - 4) (x + 1) (2x - 3)
6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.
(3x - 1)(2x2 - 2x - 1)
24x^5 + 24x^3 = 24x^3(x^2 + 1)
To factor a monomial, is to write the monomial as the product of two monomials. there are more than one possible answers when factoring For example if you had: 6x4 the answer could be -(2x3)(3x) -(2x2)(3x2) -(6x)(x3) -(x)(6x3) -(6x2)(x2)
6 multiplied by 4 is 24 here is how i did it 6x1=6 6x2=12 (you just do 6 plus another 6) 6x3=18 6x4=24 hope this helped :)